The effects of turbulence on the growth of three different diatom species - Liu, Yijing; Yu, Lin; Yao, Zhongzhi; Shen, Yunwen; Pan, Yiwen (Frontiers in Marine Science, 2024)
The effects of turbulence on phytoplankton growth have received considerable attentions. However, the complexity of turbulence poses a significant challenge to its systematic characterization in the laboratory, resulting in relatively limited data on the effects of turbulence on several algal species. Here, a laboratory turbulence simulation system was set up to systematically investigate the growth of three common diatom species (Thalassiosira pseudonana, Skeletonema costatum, and Phaeodactylum tricornutum) under stationary and turbulent conditions (at 60, 120, 180 rpm), and measurements were taken for the algal biomass, algal photosynthetic activity, and nutrients consumption. By comparing the growth of three algae species under different turbulence exposure intensities, this study found that different algae exhibit varying sensitivities to turbulence, and therefore have different shear thresholds. Meanwhile, cell morphology is the key factor influencing the different shear threshold values observed in the three diatom species. Additionally, turbulence could impact algal aggregation and light availability, and dramatically improve nutrient uptake by phytoplankton. Our study will provides theoretical support for future endeavors in using turbulence to cultivate phytoplankton or combat algal blooms.